Tahap Kemudahan Dan Penggunaan Peralatan Audio-Visual Dan Komputer Di Masjid-Masjid Di Bawah Kelolaan Jabatan Agama Islam Selangor (Jais) - Yuseri Ahmad; Marina Munira Abdul Mutalib; Mohd Azhar Ibrahim Residi; Naim Haji Ahmad (Universiti Sains Islam Malaysia, 2024)
This research is geared up to examine the availability of audio-visual equipments in numerous mosques located in Selangor. It is also to measure the fi-equency of usage of these facilities provided and the capability of the staffs to handle these equipments appropriately. The research has been conducted on 37 selected mosques particularly located in a district of city or town and run by Jabatan Agama Islam Selangor (JAIS). This is a fieldwork research whereby the methods of collecting data are mainly fiom interviews with selected respondents and based on a set of questions for questionnaire. The respondents of this research are primarily from the committees and staffs who responsible on the affairs of the mosques. The research has shown that majority of the mosques are provided with the basic equipments like microphone, cassettes on al-Quran recitations and radios. Yet, other equipments ofhighly technology are ofnon-existence in many of these mosques.